2018
DOI: 10.1038/s41598-018-31534-y
|View full text |Cite
|
Sign up to set email alerts
|

Dual action of L-Lactate on the activity of NR2B-containing NMDA receptors: from potentiation to neuroprotection

Abstract: L-Lactate is a positive modulator of NMDAR-mediated signaling resulting in plasticity gene induction and memory consolidation. However, L-Lactate is also able to protect neurons against excito-toxic NMDAR activity, an indication of a mitigating action of L-Lactate on NMDA signaling. In this study, we provide experimental evidence that resolves this apparent paradox. Transient co-application of glutamate/glycine (1 μM/100 μM; 2 min) in primary cultures of mouse cortical neurons triggers a NMDA-dependent Ca2+ si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 74 publications
2
36
0
4
Order By: Relevance
“…Lactate has been shown to play a role in enhancing neuronal survival 9,21 . These studies indicated that lactate promotes an increased ATP production and a better Ca 2+ buffering in a model of excitotoxicity.…”
Section: Results: Lactate Pre-treatment Reduces Cell Death Induced Bymentioning
confidence: 99%
“…Lactate has been shown to play a role in enhancing neuronal survival 9,21 . These studies indicated that lactate promotes an increased ATP production and a better Ca 2+ buffering in a model of excitotoxicity.…”
Section: Results: Lactate Pre-treatment Reduces Cell Death Induced Bymentioning
confidence: 99%
“…SFKs phosphorylate NMDAR subunits, which may sustain ERK activation following TrKB activation via Zn 2+ that influxes through NMDAR channels . A recent study also proved that lactate activates NR2B‐containing NMDARs, resulting in Ca 2+ influx and subsequent signaling cascade activation . We may infer that when we inject lactate in vivo, upregulation of NMDARs in certain brain regions will occur by virtue of the crucial role of NMDARs in synaptic plasticity, memory, and addiction.…”
Section: Lactate As a Signaling Moleculementioning
confidence: 94%
“…NADH is mainly derived from lactate conversion into pyruvate via LDH in the presence of NAD + as the mediator of activating NR2B‐containing NMDARs. Subsequently, increased expression of ERK and a constellation of IEGs underlying synaptic plasticity and memory may stem from the elevation of intracellular Ca 2+ or NADH . Notably, NADH and NMDA can modulate the expression of nearly 65% and 70% of genes affected by lactate, respectively, suggesting that the lactate signaling predominantly exerts its function by activation of NMDAR .…”
Section: Lactate As a Signaling Moleculementioning
confidence: 99%
See 2 more Smart Citations